Deliverable 1.6 Data Governance Framework - Hamre, Torill; Sagen, Hanne; Sandven, Stein; Danielsen, Finn; Ottersen, Geir; Beszczynska-Möller, Agnieszka; Morvik, Arnfinn; Schewe, Ingo; Enghoff, Martin (Zenodo, 2020)
This document contains a description of the Data Governance Framework for the INTAROS project, with an updated version of the Data Management Plan (DMP). The Data Governance Framework defines the procedures for how data management is carried out in the project, including the planning, conducting and monitoring the preparation and distribution of data collections. The DMP describes how new datasets collected or generated by partners in the project, will be managed according to guidelines for FAIR data management in Horizon 2020. Data governance in INTAROS is pragmatic and geared towards supporting partners in preparing and publishing their data collections. The planning and monitoring activities are carried out by the Data Management Theme Leader and the leaders of the four data generating work-packages in the project. Partners generating data are responsible for making their collections available in line with the recommendations of the DMP. The Data Management Theme Leader, data centre partners (AWI, CNRS, FMI, IMR, IFREMER, ONC, RADI, RIHMI-WDC) and the leader of WP5 (“Data integration and management”) (Terradue) are responsible for providing support with technical aspects of data publication and distribution. INTAROS is pan-Arctic in scope and collect in situ observations, extract parameters from satellite data and model projections in several regions and across multiple spheres (themes). The focus areas of INTAROS include Coastal Greenland, North of Svalbard, Fram Strait, the Eurasian Basin, and (5) selected sites in Siberia, Finland, Canada and Alaska. Within these areas, INTAROS partners are collecting new observations and generating high-level data products from different spheres: (1) Atmosphere, (2) Ocean, (3) Sea ice, (4) Marine ecosystems, (5) Terrestrial, (6) Glaciology, (7) Natural hazards, (8) Community-based monitoring. This makes datasets collected or generated within INTAROS relevant for a number of research projects as well as for infrastructures such as EMODNET and GEOSS. Datasets collected or ...